FENOMENA PENGGUNAAN SIMBOL-SIMBOL KEAGAMAAN PENGEMIS JALANAN DI KOTA MEDAN - Silalahi, Rizky Salim; Syahminan, Mhd.; Muary, Rholand (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2024)
Beggars are people who beg in public in various ways that beggars do in order to get money and goods that are useful for themselves. Begging is also usually done in crowded places such as houses of worship, red lights, markets, and people's homes. By begging someone obtains material easily and does not require the ability to work. The methodology used in this study uses a qualitative approach such as interviews with eleven beggars in the city of Medan. By processing data such as collecting information and analyzing the findings obtained. The large number of beggars in the city of Medan has a negative impact on society with low human resources, especially for religion which is a symbol of making it easier to carry out begging activities such as using caps, headscarves, koko clothes, and other Islamic clothing. The theoretical approach is carried out using the theory of Symbolic Interactionism which has a placement towards a person's way of solving problems in his life through the process of thinking and placing himself as an object and subject. The existence of cooperation between the community and the government can eliminate the phenomenon of begging which is still widely practiced by beggars, moreover Islam is made a begging religion in public, so that religious symbols may not be used for individual use.